Oral microbiome activity in children with autism spectrum disorder. Issue 9 (14th August 2018) - Hicks, Steven D.; Uhlig, Richard; Afshari, Parisa; Williams, Jeremy; Chroneos, Maria; Tierney‐Aves, Cheryl; Wagner, Kayla; Middleton, Frank A.
Abstract : Autism spectrum disorder (ASD) is associated with several oropharyngeal abnormalities, including buccal sensory sensitivity, taste and texture aversions, speech apraxia, and salivary transcriptome alterations. Furthermore, the oropharynx represents the sole entry point to the gastrointestinal (GI) tract. GI disturbances and alterations in the GI microbiome are established features of ASD, and may impact behavior through the "microbial‐gut‐brain axis." Most studies of the ASD microbiome have used fecal samples. Here, we identified changes in the salivary microbiome of children aged 2–6 years across three developmental profiles: ASD ( n = 180), nonautistic developmental delay (DD; n = 60), and typically developing (TD; n = 106) children. After RNA extraction and shotgun sequencing, actively transcribing taxa were quantified and tested for differences between groups and within ASD endophenotypes. A total of 12 taxa were altered between the developmental groups and 28 taxa were identified that distinguished ASD patients with and without GI disturbance, providing further evidence for the role of the gut‐brain axis in ASD. Group classification accuracy was visualized with receiver operating characteristic curves and validated using a 50/50 hold‐out procedure. Five microbial ratios distinguished ASD from TD participants (79.5% accuracy), three distinguished ASD from DD (76.5%), and three distinguished ASD children with/without GI disturbance (85.7%). Taxonomic pathways were assessed using the Kyoto Encyclopedia of Genes and Genomes microbial database and compared with one‐way analysis of variance, revealing significant differences within energy metabolism and lysine degradation. Together, these results indicate that GI microbiome disruption in ASD extends to the oropharynx, and suggests oral microbiome profiling as a potential tool to evaluate ASD status. Autism Res 2018, 11: 1286–1299 . © 2018 The Authors. Autism Research published by International Society for Autism Research and Wiley Periodicals LLC Lay Summary: Previous research suggests that the bacteria living in the human gut may influence autistic behavior. This study examined genetic activity of microbes living in the mouth of over 300 children. The microbes with differences in children with autism were involved in energy processing and showed potential for identifying autism status.